Curing pancreatic cancer. (November 2021) - Traub, Benno; Link, Karl-Heinz; Kornmann, Marko
Abstract: The distinct biology of pancreatic cancer with aggressive and early invasive tumor cells, a tumor promoting microenvironment, late diagnosis, and high therapy resistance poses major challenges on clinicians, researchers, and patients. In current clinical practice, a curative approach for pancreatic cancer can only be offered to a minority of patients and even for those patients, the long-term outcome is grim. This bitter combination will eventually let pancreatic cancer rise to the second leading cause of cancer-related mortalities. With surgery being the only curative option, complete tumor resection still remains the center of pancreatic cancer treatment. In recent years, new developments in neoadjuvant and adjuvant treatment have emerged. Together with improved perioperative care including complication management, an increasing number of patients have become eligible for tumor resection. Basic research aims to further increase these numbers by new methods of early detection, better tumor modelling and personalized treatment options. This review aims to summarize the current knowledge on clinical and biologic features, surgical and non-surgical treatment options, and the improved collaboration of clinicians and basic researchers in pancreatic cancer that will hopefully result in more successful ways of curing pancreatic cancer.